Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan dan Sikap WUS dalam Melakukan Pemeriksaan IVA Di Desa Pabelan - Rizki Mahanani, Putri; , Sulastri, S.Kp., M.Kes (2016)
This study aims to determine the effect of health education to increase knowledge of women of childbearing age in examinations VIA (Visual Inspection Acetic Acid) for early detection of cervical cancer. This study uses descriptive study with pre-experimental approach to design one group pre-test and post-test. This research was conducted in Puskesmas Kartasura precisely in the village Gumpang Pabelan in Dukuh Lor and was conducted in May 2016. The population in this study of 100 people, the sample in this study amounted to 78 people. Data analysis techniques using univariate and bivariate analysis by paired t-test. Results of research knowledge level of women of childbearing age about the VIA examination before treatment is given health education in the poor category and after given health education has increased with both categories. The attitude of women of childbearing age about the VIA inspection before being given health education in the poor category and after given rise to good health education. There is a significant effect of health education to improve the knowledge and attitude of women of childbearing age in examinations VIA of sig 0.001 <0.05 and sig 0.001 <0.05.